KEBIJAKAN LITERASI INKLUSIF SEBAGAI PILAR PENDIDIKAN NON-FORMAL - Rani, Berliana Mustika (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
This study aims to analyze the elements of landscape beauty and the role of local communities in supporting sustainable tourism management in Bromo Tengger Semeru National Park (TNBTS). Using a qualitative approach with a case study design, data was obtained through interviews, observations, and document analysis. The results showed that the beauty of the volcanic landscape, a combination of sand seas, sunrise, and the cultural values of the Tengger people, are the main attractions of this area. The active participation of local communities, including through the preservation of customs such as the Kasodo ceremony, contributes significantly to maintaining cultural values and ecosystems. However, challenges such as mass tourism, environmentally destructive tourist behavior, and weaknesses in area management, require strategic steps. This research emphasizes the importance of adopting ecotourism principles, increasing human resource capacity, and strengthening multi-stakeholder synergies. The contribution of this research lies in the development of a management model that integrates landscape beauty, local culture, and environmental sustainability as the basis for sustainable tourism management.